Minimally invasive spine surgery techniques, evidence and controversies - Hartl, Roger; Korge, Andreas (AOSpine, 2012)
Minimally invasive spine surgery, in some form or other, has historical roots dating back more than 100 years, and recent advances in technology now make it increasingly effective in treating suitable spine patients. While minimally invasive approaches have shown to reduce muscle damage, blood loss, and post-operative pain, to perform this t ype of surgery correctly, even highly skilled modern-day surgeons must prepare themselves for a demanding learning curve.